Program for Contact Allergen Research (PPAC) - a new tool for dermatologists - Vanessa Barreto Rocha; Carla Jorge Machado; Flávia Vasques Bittencourt (Sociedade Brasileira de Dermatologia, 2016)
Abstract: In Brazil there is no classification of dermatological products by the presence of vehicles with sensitizing potential. The objective of this study is to create a database to classify such products based on the absence of the selected allergens, aiming at making it available for medical consultation. We conducted an observational study, from the content of labels and/or inserts on the composition of 966 dermatological products in the Brazilian market. No chemical analysis was performed. The database called Programa para Pesquisa de Alérgenos de Contato (www.ppac.com.br) was created, in which safe products for patients allergic to dermatological vehicles are provided.